Multiplatform Radio: Maintaining Existence and Performing Media Functions in the Digital Age - Dinda Nur Ardilla; Andre Noevi Rahmanto; Sudarmo (PT FORMOSA CENDEKIA GLOBAL, 2023)
The pattern of public consumption of media is starting to shift to online-based platforms. Local private radio especially, has big challenges in the digital era. The focus of this study is to analyze the use of digital technology in supporting K Radio's analogue broadcasts, which is one of the local radio stations in Jember. This study uses a qualitative method with 3 data collection techniques, namely in-depth interviews, direct observation, and utilizing documents. The results showed that K Radio was quite successful in implementing media convergence to support terrestrial channels. As a news radio, K Radio also continues to carry out its function as a mass media which cannot be separated from providing information, education, entertainment and exercising social control